Robotic-Assisted Trajectory Into Kambin's Triangle During Percutaneous Transforaminal Lumbar Interbody Fusion—Initial Case Series Investigating Safety and Efficacy. Issue 6 (8th October 2021) - Dalton, Tara; Sykes, David; Wang, Timothy Y; Donnelly, Dustin; Than, Khoi D; Karikari, Isaac O; Goodwin, C Rory; Gupta, Dhanesh K; Wiggins, Walter F; Abd-El-Barr, Muhammad M
Abstract: BACKGROUND: Minimally invasive spine surgery (MISS) has the potential to further advance with the use of robot-assisted (RA) techniques. While RA pedicle screw placement has been extensively investigated, there is a lack of literature on the use of the robot for other tasks, such as accessing Kambin's triangle in percutaneous lumbar interbody fusion (percLIF). OBJECTIVE: To characterize the surgical feasibility and preliminary outcomes of an initial case series of 10 patients receiving percLIF with RA cage placement via Kambin's triangle. METHODS: We performed a single-center, retrospective review of patients undergoing RA percLIF using robot-guided trajectory to access Kambin's triangle for cage placement. Patients undergoing RA percLIF were eligible for enrollment. Baseline health and demographic information in addition to peri- and postoperative data was collected. The dimensions of each patient's Kambin's triangle were measured. RESULTS: Ten patients and 11 levels with spondylolisthesis were retrospectively reviewed. All patients successfully underwent the planned procedure without perioperative complications. Four patients underwent their procedure with awake anesthesia. The average dimension of Kambin's triangle was 66.3 m 2 . With the exception of 1 patient who stayed in the hospital for 7 d, the average length of stay was 1.2 d, with 2 patients discharged the day of surgery. No patients suffered postoperative motor or sensory deficits. Spinopelvic parameters and anterior and posterior disc heights were improved with surgery. CONCLUSION: As MISS continues to evolve, further exploration of robot-guided surgical practice, such as our technique, will lead to creative solutions to challenging anatomical variation and overall improved patient care.